Risk for development of vancomycin resistant enterococci bacteremia among colonized or infected patients, a multiple center, retrospective study in Palestine - Dana Sadaqa; Hammam Rjoup; Hasan Arafat; Ayman Shoeibet; Musa Hindiyeh; Ali Sabateen (Scientific Reports)
Abstract Vancomycin-Resistant Enterococcus (VRE) is one of the key antibiotic-resistant pathogens that challenges the health system with its threat to human health. Most VRE infections occur in hospital settings as these pathogens are known to colonize hospital environments and maintain their viability for long periods. Without good infection control measures, these pathogens can spread in the hospital setting and cause hospital-acquired infections including bacteremia. In this study, we report the isolation of VRE from patient samples hospitalized in four Palestinian hospitals. The American Society for Microbiology proceedings were utilized to culture and identify VRE. During the 5-year study period between December 2020 and March 2024, 736 VRE isolates were detected, and 30 (4.76%) patients with bacteremia were reported. Excellent infection control measures including active surveillance swabs, contact precaution and following strict isolation protocols were important to limit the spread of these pathogens, as well as limiting the consumption of antibiotics, especially Vancomycin. In this research article, we discuss the detection of VRE in the different hospitals located in West Bank and East Jerusalem. We also analyze the prevalence of VRE in other body sites including anal surveillance swab, urine, wound and stool cultures that may be associated with developing VRE bacteremia. The cumulative average of VRE causing bacteremia was of urinary origin, followed by wound and stool positive cultures, respectively. Hospital number 2 had the highest risk of developing bacteremia in patients with other VRE positive culture or swab with a percentage of 11.3%.